MODERN TRENDS OF FORMATION OF THE TOURISM INDUSTRY IN THE ELECTRONIC ENVIRONMENT AS A DRIVER OF THE DEVELOPMENT OF THE RUSSIAN ECONOMY - O. E. Pudovkina; S. V. Sharokhina (Вестник университета, 2019)
The relevance of the topic under study is due to changes in the global society of the key factors of economic development, which are the evolution of information and communication technologies. This evolution has radically transformed into a global tourism industry, offering new development prospects, especially in terms of increasing its competitiveness. As Russia declares itself as a country pursuing the progress of the information society, there is currently a need for an understanding of the concept of e-tourism and the introduction of information and communication technologies (ICT) in the field of tourism services. The study has been carried out in the article to identify critical factors of entry into the electronic environment for Russian travel companies based on the use of the website rating index (WAI) and the Facebook index (FAI). As a result of the analysis, a system was developed for the effective interaction of the main actors in tourism based on the creation of a single portal for registration and implementation of tourist services.